Inclusive education in Mexico: from theory to practice - Mendoza Méndez, Luz Areli (2018)
At present, there is a discussion in Mexico about working with diversity focusing on inclusive education. However, there is a question upon how is it being implemented. From the perspective of a support teacher, this paper approaches to some of the legal and normative basis of inclusive education. Moreover, there is also a reflection on some theoretical propositions and its practical application on schools.